Promise of shadows a novel - Ireland, Justina (Simon & Schuster BFYR, 2014)
As a human/god offspring, Zephyr Mourning is destined for a life of servitude but when she uses a forbidden dark power to kill the minor god who murdered her sister she is sent to Tartarus, where she discovers that she may be the Nyx, a dark goddess prophesied to change the balance of power